Single-Cell Transcriptomics Reveals Peripheral Immune Responses in Anti-Synthetase Syndrome-Associated Interstitial Lung Disease - Zhu, Lili; Cao, Zhong; Wang, Shiyao; Zhang, Changshui; Fang, Lei; Ren, Yanhong; Xie, Bingbing; Geng, Jing; Xie, Sheng; Zhao, Ling; Ma, Li; Dai, Huaping; et al. (Frontiers in Immunology, 2022)
Objective: Interstitial lung diseases (ILDs) secondary to anti-synthetase syndrome (ASS) greatly influence the prognoses of patients with ASS. Here we aimed to investigate the peripheral immune responses to understand the pathogenesis of this condition. Methods: We performed single-cell RNA sequencing (scRNA-seq) of peripheral blood mononuclear cells (PBMCs) from 5 patients with ASS-ILD and 3 healthy donors (HDs). Flow cytometry of PBMCs was performed to replenish the results of scRNA-seq. Results: We used scRNA-seq to depict a high-resolution visualization of cellular landscape in PBMCs from patients with ASS-ILD. Patients showed upregulated interferon responses among NK cells, monocytes, T cells, and B cells. And the ratio of effector memory CD8 T cells to naïve CD8 T cells was significantly higher in patients than that in HDs. Additionally, Th1, Th2, and Th17 cell differentiation signaling pathways were enriched in T cells. Flow cytometry analyses showed increased proportions of Th17 cells and Th2 cells, and decreased proportion of Th1 cells in patients with ASS-ILD when compared with HDs, evaluated by the expression patterns of chemokine receptors. Conclusions: The scRNA-seq data analyses reveal that ASS-ILD is characterized by upregulated interferon responses, altered CD8 T cell homeostasis, and involvement of differentiation signaling pathways of CD4 T cells. The flow cytometry analyses show that the proportions of Th17 cells and Th2 cells are increased and the proportion of Th1 cells is decreased in patients with ASS-ILD. These findings may provide foundations of novel therapeutic targets for patients with this condition.